Legal Feasibility of Trademark Certificates as Credit Collateral and Its Implications for Indonesian MSMEs - Stephanie Devty (Veteran Law Review, 2026)
This article examines the legal feasibility of using trademark certificates as credit collateral in Indonesia and highlights the practical challenges arising from their application within the financing landscape of Micro, Small, and Medium Enterprises (MSMEs). It analyzes how trademark-based collateral fits within Indonesia’s existing credit and intellectual property framework. Employing normative legal research with a statute-based and doctrinal approach, this study focuses on the structure and substance of Indonesian trademark and collateral law, supported by qualitative analysis of relevant legal materials. The findings indicate that trademark rights, as exclusive, transferable, and economically valuable assets, meet the legal requirements to function as credit collateral. However, their practical implementation remains constrained by the absence of standardized valuation mechanisms, uncertainty in enforcement procedures, prudential banking practices, and the limited readiness of MSMEs. The originality of this research lies in its emphasis on legal feasibility and normative-regulatory challenges, offering a distinct perspective on intellectual property-based financing beyond purely economic valuation